Numerical heat transfer study of an impinging jet of nanofluid of TiO2 on a chip surface - Kanokjaruvijit, Koonlaya; Othaganont, Pongpun; Panyadibwong, Suttinon; Tuamjan, Kamolthip; Srirat, Pimwipa; Rattanasangsri, Taechinee (Naresuan University Engineering Journal, 2022)
A numerical investigation of 2D axisymmetric heat transfer of an impinging jet of water-based titanium dioxide (TiO2) nanofluid on a CPU chip surface is performed by using the finite element method with k-e turbulence model with the wall treatment. The flat plate impingement is also studied to compare the heat transfer and flow characteristics with those of the chip plate and the average heat transfer results agree well with the experimental results obtained from literature. Parametric effects such as nanofluid concentration (f), Reynolds number (ReDj) and jet-to-plate spacing (H/Dj) are examined. The nanofluid concentration is in the range of 0-6% by volume. The tested ReDj is between 2000 and 8000. The jet-to-plate spacing is between 2-4. The maximum heat transfer enhancement in terms of average Nusselt number of the TiO2 nanofluid compared to that of the water is 18.24% for the chip plate impingement at ReDj = 2000 and f = 6%; however, this maximum enhancement is 47.13% in terms of the average heat transfer coefficient. After the multiple linear regression analysis, the nondimensional heat transfer correlations are obtained. Finally, the ratios of pumping power between nanofluid and base fluid are plotted and found the penalty of 1.5 to nearly 4 times.